A Sensitive Determination of Carbofuran by Spectrophotometer using 4, 4-azo-bis-3, 3′5, 5′-tetra bromoaniline in various Environmental Samples. Issue 2 (2006) - Bhargavi, O.; Kiran, K.; Suvardhan, K.; Rekha, D.; Janardhanam, K.; Chiranjeevi, P.
Abstract : A simple and sensitive spectrophotometric technique was developed for the determination of carbofuran in its formulations, water and grain samples. The method was based on the alkaline hydrolyzed product of carbofuran phenol interacted with diazonium salt of 4, 4-azo-bis-3, 3′5, 5′-tetra bromo aniline. The maximum absorbance of the red coloured derivative was measured at 470 nm. The beer's law was obeyed in the concentration range of 0.1-16.0 µg/mL. The interference of the non target species were studied on the determination of carbofuran which increases the selectivity of the method. The present method was successfully applied for the determination of carbofuran in its formulations, water and grain samples.